Bilateral primary choroidal melanoma. Issue 4 (April 1984) - Migdal, C; Macfarlane, A
Abstract : A case of bilateral primary choroidal melanoma is described in a 51-year-old white male. Histological confirmation followed enucleation of the left eye and local excision in the right. A careful systemic evaluation failed to demonstrate any other primary or secondary melanomata. This case is the first bilateral primary choroidal melanoma reported in the United Kingdom and the first to be described in which histological confirmation was obtained as a result of local excision of one of the tumours.